2022
DOI: 10.3389/fbioe.2022.990249
|View full text |Cite|
|
Sign up to set email alerts
|

Preparation and characterization of polyethylene glycol/chitosan composite water-based wound healing lubricant

Abstract: The proportion of pregnant women giving birth through cesarean section is increasing annually worldwide. However, post-cesarean section scar diverticulum is a common condition that occurs and requires better surgical strategies than the methods currently used. We hypothesized that using biological lubricant topically on the incision area during C-section could be an option to minimize the scar. This water-based polyethylene glycol (PEG)/chitosan (CS) composite lubricant was prepared via ultrasonic blending. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In the environment, PEG does not cause pollution to soil, water, and air because it is broken down into smaller molecules by microorganisms. In the biological body, PEG can also be hydrolyzed by enzymes into harmless substances such as water and carbon dioxide, which will not cause harm to the human body (Gao et al 2022 ). Some studies have shown that methanogenic bacteria can degrade PEG (Dwyer et al 1983 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the environment, PEG does not cause pollution to soil, water, and air because it is broken down into smaller molecules by microorganisms. In the biological body, PEG can also be hydrolyzed by enzymes into harmless substances such as water and carbon dioxide, which will not cause harm to the human body (Gao et al 2022 ). Some studies have shown that methanogenic bacteria can degrade PEG (Dwyer et al 1983 ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that adding PEG can not only affect the biosynthesis of cellulase, but also reduce the adsorption capacity of cellulase to lignin so as to reduce the enzyme loading and promote the effective combination of enzyme and substrate (Luo et al 2017 ). In addition, compared with organic solvent inducers such as N,N -dimethylformamide (DMF) (Chen et al 2019 ), PEG has good biocompatibility and biodegradability (Gao et al 2022 ), which ensures the safety of the biological process and the enzyme produced.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed two peaks for Si 2p at 102.6 eV and 103.5 eV, which are associated with the Si–OH and Si–O–Si bonds. 39–45…”
Section: Resultsmentioning
confidence: 99%
“…We also observed two peaks for Si 2p at 102.6 eV and 103.5 eV, which are associated with the Si-OH and Si-O-Si bonds. [39][40][41][42][43][44][45] Electrochemistry and ECL of the modified electrodes showed the maximum ECL intensity at +1.12 V vs. Ag/AgCl. As can be seen in Fig.…”
Section: Fe-sem Analysismentioning
confidence: 98%